2015
DOI: 10.1097/mog.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Gastroparesis

Abstract: The relationship between delay in gastric emptying, symptom pattern, and response to prokinetic therapy in gastroparesis is poor. In diabetes, gastroparesis is characterized by loss of ICCs, and this is inversely correlated to the number of CD206+ macrophages. Dietary interventions may help to alleviate symptoms. Tricyclic antidepressants do not provide symptomatic benefit to patients with idiopathic gastroparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 49 publications
2
61
1
3
Order By: Relevance
“…In our study, only 4.5% of diabetic patients had abnormal results of gastroscopy (except for Helicobacter pylori infection). This observation is similar to the results of other studies in which dyspepsia has been found to be predominantly functional in diabetes, and long-term poor metabolic control in diabetes leads to the development of gastroparesis [8,9,11]. Osicipenko et al showed that dyspepsia affects up to 71% of patients with type 2 diabetes, and in 42%, organic changes in the digestive tract were confirmed [8].…”
Section: Discussionsupporting
confidence: 89%
“…In our study, only 4.5% of diabetic patients had abnormal results of gastroscopy (except for Helicobacter pylori infection). This observation is similar to the results of other studies in which dyspepsia has been found to be predominantly functional in diabetes, and long-term poor metabolic control in diabetes leads to the development of gastroparesis [8,9,11]. Osicipenko et al showed that dyspepsia affects up to 71% of patients with type 2 diabetes, and in 42%, organic changes in the digestive tract were confirmed [8].…”
Section: Discussionsupporting
confidence: 89%
“…PGS is a disorder of the gastrointestinal tract and a common complication after abdominal surgery. Traditional medical therapy for PGS includes behavioral and dietary modification, nasogastric tube suction, and administration of prokinetic drugs . The few patients who fail to benefit from these therapies and continue to have the debilitating symptoms of PGS may only benefit from additional surgery .…”
Section: Discussionmentioning
confidence: 99%
“…Postsurgical gastroparesis syndrome (PGS) is a complex gastric motility disorder, defined as the delayed emptying of gastric solids in the absence of mechanical obstruction. Characteristic symptoms include nausea, vomiting, epigastric pain, early satiety, and anorexia . PGS is a common complication of distal gastric resection and occurs in approximately 0.4–5.0% of post‐gastrectomy patients .…”
Section: Introductionmentioning
confidence: 99%
“…Delayed gastric emptying and slowed colonic transit are the common characteristics in diabetic patients with gastrointestinal motility disorder . Although accompanied symptoms such as nausea, vomiting, early satiety, abdominal pain, and constipation greatly affect their life quality, various therapies are unsatisfactory for their few positive outcome and limitation in duration.…”
Section: Introductionmentioning
confidence: 99%